The Role of Organizational Culture, Market Competition, Mitigation Strategies and Information Systems on Risk Management - Indra Wahyu Putra, Christophorus; Marinda Machdar, Nera; Haymans Manurung, Adler (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
The purpose of this literature research is to help hypotheses for future authors in determining research related to risk management. Research articles on the role of organizational culture, market competition, mitigation strategies and information systems on risk management are scientific literature articles within the scope of risk management. The approach used in this literature review research is descriptive qualitative. The data collection technique is to use literature studies or review relevant previous articles. The data used in this descriptive qualitative approach comes from previous research relevant to this research and sourced from academic online media such as Thomson Reuters Journals, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Springer, Web of Science, Sinta Journals, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, 1 relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Organizational Culture plays a role in Risk Management; 2) Market Competition plays a role in Risk Management; 3) Mitigation Strategies play a role in Risk Management; and 4) Information Systems play a role in Risk Management.